FENOMENA DAN KONTROVERSI HAK CIPTA KASUS PENCURIAN KESENIAN REOG PONOROGO - Putri, Arinda Emilia; Chusna, Miftachul; Nurhafiza, Nurhafiza; Sabila, Hafilda (Studi Budaya Nusantara, 2019)
ABSTRACT Regional freedom changes from various angles, replacing the entry of no-outs that challenge local identity. However, political decentralization in Indonesia and the transfer of authority in the field of education and development into the hands. In this context, in 2007 there was controversy in Indonesia about one of the traditional languages originating from Ponorogo Regency. The controversy is based on the perception of the people of Ponorogo and the wider community in Malaysia who claim the Reog Ponorogo art through the inclusion of the art in an advertisement in Malaysia. The purpose of this research is to know the importance of Reog as a Ponorogo identity and understand the cause of the controversy about the reog protection. This research is a qualitative research, data obtained through interviews with informants (Head of the Culture and Tourism Office of Culture Tourism) is the main technique in the process of collecting data in this study. The results showed a misunderstanding caused by lost communication. Understanding the Indonesian people Ponorogo community they think that Reog is really claimed by Malaysia.